Wired/wireless Internet communications 9th IFIP TC 6 International Conference, WWIC 2011, Vilanova i la Geltrú, Spain, June 15-17, 2011: proceedings - WWIC 2011 Vilanova i la Geltrú, Spain) (2011; Masip-Bruin, Xavier; SpringerLink (Online service). (Heidelberg Springer, 2011)
This book constitutes the proceedings of the 9th IFIP TC 6 International Conference on Wired/Wireless Internet Communications, WWIC 2011, held in Vilanova i la Geltrú, Spain, in June 2011. The 26 contributions included were carefully reviewed and selected from 50 submissions. In addition the book contains 15 invited papers. The contributions are structured in topical sections on mobility and LTE networks; performance and simulation analysis; adaptive approaches to guarantee E2E network services; energy efficiency and cooperation in wireless networks; transmission and management; quality through routing, naming and control; wireless multi-hop communications challenges in the future internet; and emerging contribution
Electronic reproduction.
Keywords: Wireless Internet -- Congresses; Mobile communication systems -- Congresses; Electronic book